2015
DOI: 10.1590/0100-67622015000100011
|View full text |Cite
|
Sign up to set email alerts
|

FISIOLOGIA DA GERMINAÇÃO DE SEMENTES DE Dalbergia nigra(Vell.) Allemão ex Benth. SOB DIFERENTES TEMPERATURAS E TEMPOS DE EXPOSIÇÃO

Abstract: 4RESUMO -A germinação de sementes é dependente de fatores abióticos, sendo a temperatura um dos principais, cuja influência, em condições extremas, causa danos às sementes. Este trabalho teve por objetivo investigar o efeito das diferentes temperaturas durante a germinação de Dalbergia nigra e suas implicações na fisiologia das sementes. Avaliaram-se o percentual de germinação, o índice de velocidade de germinação (IVG) e a integridade de membranas celulares pelo teste de condutividade elétrica de sementes em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 29 publications
3
9
0
7
Order By: Relevance
“…Similar results have also been reported for SOD activity in Medicago sativa seeds, which showed constant behavior at 22 • C [48]. During the soaking of Dalbergia nigra seeds, SOD activity is higher at 45 • C than at 25 • C [18]. Nevertheless, Kumar et al [49] observed an increase in SOD activity until 40 • C in maize and rice genotypes, followed by a decrease after 45 • C. Although the production of SOD is one of the first responses to abiotic stress, the action of this enzyme must not be evaluated individually, since APX and/or CAT, for instance, eliminate H 2 O 2 , which permeates the membrane easily and is toxic to cells [50].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have also been reported for SOD activity in Medicago sativa seeds, which showed constant behavior at 22 • C [48]. During the soaking of Dalbergia nigra seeds, SOD activity is higher at 45 • C than at 25 • C [18]. Nevertheless, Kumar et al [49] observed an increase in SOD activity until 40 • C in maize and rice genotypes, followed by a decrease after 45 • C. Although the production of SOD is one of the first responses to abiotic stress, the action of this enzyme must not be evaluated individually, since APX and/or CAT, for instance, eliminate H 2 O 2 , which permeates the membrane easily and is toxic to cells [50].…”
Section: Discussionsupporting
confidence: 87%
“…The increased concentration of this molecule might lead to the occurrence of lipid peroxidation and to an ulterior disruption of the cell membrane, as indicated by the increased leakage at 45 • C, which caused a gradual decrease in seed viability. Similar results were found in Dalbergia nigra seeds, which showed a gradual loss in viability at 45 • C [18]. With increasing stress, the formation of ROS is intensified, and their elimination must be constant to avoid oxidative stress.…”
Section: Discussionsupporting
confidence: 80%
“…The germination speed index (GSI) is a vigor indicator of the seeds and of the germinating potential under adverse conditions (Matos et al, 2015). A positive and highly significant correlation between the seed mass and GSI (r p =0.93 and p-value=0.001) was found in the eight peach rootstocks evaluated.…”
Section: Germination Potential Of Seeds Without Endocarpsmentioning
confidence: 97%
“…Due to difficulties found concerning germination among forest species, alternative tests, like water imbibition curve and electrical conductivity tests under controlled conditions are being applied in many laboratories with the objective of defining seed vigor and viability. The fastness in obtaining reliable results is one of the main aspects considered in the evaluation of seed quality, for it allows agility in decision making, enables its use in wider scales, decreasing the risks and costs in operations like harvest, processing, storage and commercialization (Barbieri, Menezes, Conceição, & Tunes, 2012;Hilst, Dias, Alvarenga, & Souza, 2012;Matos, Borges, & Silva, 2015).…”
mentioning
confidence: 99%